Effect of Artesunate on Behavioral Functions in Experimental Model of Alzheimer’s Disease - Chaitali Pattanayak; Sunil Kumar Patanaik; Vartika Srivastava; Mangala Charana Das; Sougata Sarkar (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Introduction: Alzheimer’s disease (AD) is a common form of dementia, causing loss of memory and cognitive impairment because of progressive neurodegeneration. Current treatment modalities for AD do not cure the disease completely, are expensive, and are associated with numerous adverse effects. Artesunate is a semisynthetic product of artemisinin, derived from the plant Artemisia annua and used conventionally to fight malaria for a long time in Chinese medicine. Artesunate is a multipotent agent with a wide array of actions. Methodology: The study was conducted in the animal house of the Department of Pharmacology, KIMS, Bhubaneswar, after getting approval from the Institutional Animal Ethics Committee. A total of 36 albino Wistar rats weighing 150–200 gms were selected for the study and divided into six groups containing six rats each. Group I was the normal control, and rats received only normal saline and regular food, whereas group II rats were disease control and received aluminum chloride only. Group III rats were the standard control group and received donepezil hydrochloride along with aluminum chloride, whereas groups IV, V, and VI were the test treatment control group receiving graded doses of artesunate along with aluminum chloride. The behavioral parameters were assessed through the morris water maze, elevated plus maze, actophotometer, and passive avoidance tests. Results: Artesunate treatment group showed considerable improvement in behavioral functions, and this effect was comparable with a standard group at the highest selected dose. Conclusion: Artesunate demonstrated neuroprotective effects through various possible mechanisms. Hence, artesunate might be therapeutically useful in neurogenerative disorders.